Pertanggungjawaban Pidana terhadap Pelaku Abortus Provocatus Criminalis (Tindak Pidana Aborsi) - Rini Wulandari (Fakultas Hukum Universitas Islam Jember, 2019)
Abortion is abortion, the release of the results of conception or fertilization prematurely. Unintentional fetal loss usually occurs in young pregnancies (one to three months). Sometimes a woman's pregnancy can die on its own without an act or intentional act. This is often referred to as